INTOLERÂNCIA CONTRA RELIGIÕES DE MATRIZ AFRICANA E A PRÁTICA DO SACRIFÍCIO - Julia Paulo Pereira (Revista Eletrônica da OAB-RJ, 2025)
O presente artigo cuida de debater a intolerância religiosa contra religiões de matriz africana, problematizando o contexto histórico dessa intolerância, que ilustra uma modalidade de racismo estrutural. Ademais, este artigo enfatiza a intolerância aos rituais de sacrifício praticados, principalmente, pelo Candomblé. Abstract Abstract. This article discusses religious intolerance against religions of African origin, problematizing the historical context of this intolerance that illustrates a modality of structural racism. In addition, the present article emphasizes the intolerance to the rituals of sacrifice practiced mainly by Candomblé. Keywords: Religious intolerance. Sacrifice of animals. Structural racism.